2021
DOI: 10.1021/acsnano.1c05619
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Fracture Propensity in Amorphous Alumina from Its Static Structure Using Machine Learning

Abstract: Thin films of amorphous alumina (a-Al2O3) have recently been found to deform permanently up to 100% elongation without fracture at room temperature. If the underlying ductile deformation mechanism can be understood at the nanoscale and exploited in bulk samples, it could help to facilitate the design of damage-tolerant glassy materials, the holy grail within glass science. Here, based on atomistic simulations and classification-based machine learning, we reveal that the propensity of a-Al2O3 to exhibit nanosca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Next, we therefore attempt to decipher how the spatial environment around the P 2 S 6 4– , P 2 S 7 4– , and PS 4 3– anions affect the lithium transport in the present glasses. To this end, we correlate the local structure and dynamics by using the “softness” , concept, which is based on classification-based machine learning to investigate the relationship between the mobility of lithium and the local environment in which it is located. Specifically, we use logistic regression to build a hyperplane (that separates “mobile” from “immobile” lithium ions) based on the static structure and corresponding rearrangement of each lithium atom at 300 K as obtained from the MD simulations to identify their mobility.…”
mentioning
confidence: 99%
“…Next, we therefore attempt to decipher how the spatial environment around the P 2 S 6 4– , P 2 S 7 4– , and PS 4 3– anions affect the lithium transport in the present glasses. To this end, we correlate the local structure and dynamics by using the “softness” , concept, which is based on classification-based machine learning to investigate the relationship between the mobility of lithium and the local environment in which it is located. Specifically, we use logistic regression to build a hyperplane (that separates “mobile” from “immobile” lithium ions) based on the static structure and corresponding rearrangement of each lithium atom at 300 K as obtained from the MD simulations to identify their mobility.…”
mentioning
confidence: 99%
“…The researchers recently identified that the nanoscale ductility propensity is inherent in the static (nonstrained) structure of amorphous Al 2 O 3 by utilizing atomistic simulations and classification-based machine learning techniques (Figure 21h). 120 The study introduced a novel "softness" metric derived from machine learning, which can predict bond switching tendencies based on the static structure. Intriguingly, this softness metric was trained using spontaneous system dynamics (i.e., under zero strain) but could effectively predict the fracture behavior of the glass (i.e., under strain).…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…(g) is adapted with permission from ref Copyright 2021, American Chemical Society. (h) is adapted with permission from ref . Copyright 2021, American Chemical Society.…”
Section: Theoretical Studies For Amorphous Nanomaterialsmentioning
confidence: 99%
“…[ 205,58 ] Very recently, it has also been shown that this metric can be trained from the spontaneous dynamics of glass under zero strain, and then used to predict the glass’ fracture propensity under strain. [ 206 ] In particular, rapid crack propagation occurs upon the local accumulation of high‐softness regions. As these studies suggest, advances in new oxide glass composition design are expected to come from coupling knowledge of nanoscale deformation processes with high‐throughput ML methods.…”
Section: Emerging Glass Types With Optical Transparency and Tailored ...mentioning
confidence: 99%